2008
DOI: 10.1017/s0031182007004064
|View full text |Cite
|
Sign up to set email alerts
|

Sex-dependent toxoplasmosis-associated differences in testosterone concentration in humans

Abstract: Several lines of indirect evidence suggest that subjects with latent infection of the coccidian parasite Toxoplasma gondii have a higher concentration of testosterone than uninfected controls. Here, we searched for direct evidence of latent toxoplasmosis-associated differences in testosterone concentration among a population of 174 female and 91 male students screened for Toxoplasma infection. We have found Toxoplasma-infected men to have a higher concentration of testosterone and Toxoplasma-infected women to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
117
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(128 citation statements)
references
References 26 publications
10
117
1
Order By: Relevance
“…The present study showed that Toxoplasma infected men had a higher concentration of testosterone than Toxoplasma free controls. This result was in agreement with previous study by (Flegr et al 2008). High concentrations of TTH and FTH have immunosuppressive effects characterized by lower cellular immunity (Roberts et al 2001).…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…The present study showed that Toxoplasma infected men had a higher concentration of testosterone than Toxoplasma free controls. This result was in agreement with previous study by (Flegr et al 2008). High concentrations of TTH and FTH have immunosuppressive effects characterized by lower cellular immunity (Roberts et al 2001).…”
Section: Discussionsupporting
confidence: 94%
“…Their tendency to disregard rules of their society which can result in lower hygienic standards and, corresponding increased risk of contact with a source of infection (Kanková et al 2011). On the other hand Flegr et al (2008) showed that Toxoplasma infected men had a higher concentration of testosterone while women had a lower concentration in comparison to control group. He explained such opposite direction of the testosterone shift in men compared to women to the gender specificity of behavioral shifts in Toxoplasma infected subjects.…”
Section: Discussionmentioning
confidence: 86%
“…Reproductive implications of T. gondii seropositivity have also been reported in rodents, with T. gondii-infected male rats being preferentially chosen as mates over the non-infected males by non-infected female rats, potentially due to changes in testosterone levels [82]. Testosterone levels have also been reported to be higher in T. gondii-infected men and decreased in T. gondii-infected women [83], and this may explain the increased impulsivity and reduced self-control findings in men. Gender differences in hedonic ratings to cat urine odor in T. gondii-infected men vs. T. gondii-infected women [84] have also been described previously.…”
Section: Discussionmentioning
confidence: 92%
“…In chronically infected rats hypomethylation of the arginine vasopressin gene promoter region was observed in the amygdala [50]. Published data has reported both increased and decreased testosterone associated with T. gondii seropositivity in humans [51][52][53].…”
Section: Hormonal Changes With Chronic Infectionmentioning
confidence: 99%